Endothelial progenitor cells as a new agent contributing to vascular repair - Miller-kasprzak, Ewa; Jagodziski, Pawe P (Archivum Immunologiae et Therapiae Experimentalis, 2007)
A special type of stem cells, defined as endothelial progenitor cells (EPCs), has been found in the bone marrow and peripheral blood. These EPCs are incorporated into injured vessels and become mature endothelial cells during re-endothelialization and neovascularization processes. Though a complete phenotypic description of EPCs remains unclear, these cells express several surface markers, the most relevant including CD34 and CD133 antigens. Furthermore, EPCs derived from other sources could also give rise to mature endothelial cells, which makes this group of cells more diverse. The recruitment of EPCs from the bone marrow to homing sites of vasculogenesis is subject to regulation by many factors, including chemokines and growth factors. The precise mechanism of EPC mobilization and differentiation is not entirely elucidated and is still under investigation. Recent studies have suggested that EPCs may promote local angiogenesis by secreting angiogenic growth factors in a paracrine manner. The number and function of EPCs can be affected during pathological conditions, including diabetes mellitus, cardiovascular risk factors for ischemic disease, and graft vasculopathy. Additionally, EPC number and migration capacity could be improved by such factors as drugs, physical exercise, and growth factors. Transplantation of EPCs into ischemic tissues may emerge as a promising approach in the therapy of diseases associated with blood vessel disorders.